FRI0023 CARDIOVASCULAR RISK AND VITAMIN D DEFICIENCY IN PATIENTS WITH RHEUMATOID ARTHRITIS IN THERAPY WITH TNF-ALPHA INHIBITORS. (June 2019) - Anghel, Daniela; Otlocan, Livia; Negru, Maria Magdalena; Bursuc, Raluca; Manolache, Anca; Busuioc, Elena; Smedescu, Valeriu; Anghel, Adrian; Plesa, Florentina Cristina; Jurcut, Ciprian
Abstract : Background: Cardiovascular disease is the main cause of mortality and morbidity in patients with rheumatoid arthritis (RA). Correlation between vitamin D deficiency and atherosclerosis in patients with rheumatoid arthritis is a subject of medical interest. Objectives: We studied the correlation between vitamin D deficiency, body mass index (BMI) and carotid intima-media thickness (CIMT) in patients with rheumatoid arthritis with anti tumor necrosis factor-alpha (TNF-α) therapy. Methods: Our study included 75 RA patients with anti-TNF-alpha therapy (Adalimumab, Influximab, Etanercept) and 30 RA patients with DMARDs (Methotrexate/Leflunomide). The patients were diagnosed with RA according to ACR/EULAR (2010) classification criteria. CIMT was measured using high-resolution Doppler ultrasonography. CIMT ≥ 0.9 mm is considered as a marker of atherosclerosis. Vitamin D deficiency was defined as serum 25-OH-vitamin D level <20 ng/mL. Other parameters included are age, body mass index (BMI=18, 5-24, 9kg / m 2 - normal weight; BMI≥25kg /m 2 - overweight) and disease activity (DAS28<2.6: remission; DAS28=2.6-3.2: low disease activity, DAS28= 3.2-5.1 : moderate disease activity; DAS28 >5.1: high disease activity). Patients with current use of vitamin D supplements were excluded. Results: The anti-TNF group included 29 patients with Adalimumab (38.7%), 25 with Etanercept (33.3%) and 21 patients in treatment with Infliximab (28%). Their mean age was 52.0 years. We evaluated patients at baseline and after 12 months with treatment. In anti-TNF group we found 9 patients (12%) with normal BMI and normal vitamin D level correlated with high CIMT (p=0.001), 21 patients (28%) with overweight and normal vitamin D level correlated with high CIMT (p=0.003), and 31 patients (41.3%) with overweight and low vitamin D level correlated with high CIMT (p=0.001). 14 patients (18.7%) with normal vitamin D level and normal weight (9) or overweight (5) were correlated with normal CIMT (p=0.01). In DMARDs group we followed the same correlation. Patients with normal BMI and normal vitamin D level had a low correlation with CIMT increase (p=0.01). Patients with overweight and low vitamin D level had a significant correlation with CIMT increase (p=0.003) than group with anti-TNF-alpha therapy. After 12 months of therapy, patients treated with Adalimumab had lower CIMT levels than patients treated with Etanercept. Conclusion: Rheumatoid arthritis patients treated with TNF inhibitors and with vitamin D deficiency but with normal BMI have been correlated with lower increase of CIMT than patients with DMARDs therapy. Normal vitamin D level was associated with low increase of CIMT in these patients. Deficiency of Vitamin D associated with overweight are risk factors for carotid atherosclerosis in patients with RA. Disclosure of Interests: None declared